FEMINIST PERSPECTIVES ON FILM “RAYA AND THE LAST DRAGON”: (A STUDY OF RELATIONAL EMPOWERMENT) - Pramesniradjati, Mikhaella Gita; Widyahening, Ch. Evy Tri (English Education Department Slamet Riyadi University Surakarta, 2025)
Abstract: This study uses Jo Rowlands' idea of relational empowerment to examine feminist readings of Raya and the Last Dragon (2021). The film presents empowerment as a collaborative attempt focused on trust, cooperation, and leadership, in contrast with typical narratives of lone female heroes. This study focuses at significant circumstances that highlight decision-making, resistance of gender norms, collaboration and reconciliation using qualitative analysis and library research. The results show that Raya's leadership, determination, and intelligence challenge gender stereotypes, and that the Southeast Asian setting of the film emphasize a collective approach to empowerment in contrast to Western individualist feminism. Keywords: Feminism, Women Empowerment, Relational Empowerment, Raya and the Last Dragon Abstrak: Studi ini menggunakan konsep pemberdayaan relasional Jo Rowlands untuk menganalisis pembacaan feminis terhadap Raya and the Last Dragon (2021). Film ini menampilkan pemberdayaan sebagai upaya kolaboratif yang berfokus pada kepercayaan, kerja sama, dan kepemimpinan, berbeda dengan narasi khas pahlawan perempuan yang bertindak sendiri. Studi ini meneliti momen-momen penting yang menyoroti pengambilan keputusan, perlawanan terhadap norma gender, kerja sama, dan rekonsiliasi dengan menggunakan analisis kualitatif dan studi pustaka. Hasil penelitian menunjukkan bahwa kepemimpinan, keteguhan, dan kecerdasan Raya menantang stereotip gender, serta bahwa latar budaya Asia Tenggara dalam film ini menekankan pendekatan pemberdayaan yang kolektif, berbeda dengan feminisme individualis Barat. Kata kunci: Feminism, Pemberdayaan Perempuan, Pemberdayaan Relasional, Raya and The Last Dragon